Pendampingan Keluarga Dalam Pemanfaatan Pojok ASI Sebagai Upaya Peningkatan Gizi Balita Di Desa Balibo Kabupaten Bulukumba - Amina Ahmad; Wanti Aotari (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2022)
Infants and Toddlers are the next generation of the nation which is very important to pay attention to the quality of their health. Special attention to nutritional adequacy in the toddler period is very important. Toddler growth and development is not as fast as in the Infant period. In general, baby weight gain will be easier to get than when toddlers. The nutritional adequacy of Toddler nutrition is influenced by several factors, both direct and indirect factors. This community service was carried out at the Mawar Posyandu, Balibo Village, Kab. Bulukumba by utilizing the ASI Corner as an effort to improve toddler nutrition. The implementation of this community service is carried out by the method of providing health education through a lecture mechanism, question and answer, direct practice of correct breastfeeding, provision and storage of expressed breast milk and a balanced menu for adequate nutritional intake of Toddlers. The results of this activity are very useful for increasing the knowledge and skills of mothers. The results of the evaluation during the activity process were found that the mother had understood and knew how to use the breast milk corner to improve toddler nutrition. With this mentoring activity, it is hoped that it will increase the knowledge of mothers so that they can breastfeed and do not experience interference in the breastfeeding process so that the exclusive breastfeeding program can be achieved.